Public Relations Marketing Strategy In Improving Product Brand Image Through Instagram (@Wings_indonesia) - Akbar, Adam Ali; Umer, Saiyed (Sinergi International Journal of Communication Sciences, 2023)
PT Sayap Mas Utama (Wings Group) 'Wings' has become a large company that exports its products worldwide since its establishment 60 years ago in East Java and is engaged in retail. In this study, the author uses Instagram and its features that exist for the implementation of Marketing Public Relations of Product Wings in making strategies to improve brand image at PT Sayap Mas Utama (Wings Group). The approach with consumers is carried out qualitatively. This type of research uses qualitative methods with in-depth interview techniques. The results of research conducted by researchers show that Wings is still lacking in promotions using Instagram, especially promotions in introducing Wings products because the content posted on Instagram shows more only for the celebrating of religious holidays, or national holidays. Meanwhile, Instagram can have a big impact on improving the brand image of the Wings Group.